Can the teaching factory model improve the entrepreneurial intentions of vocational high school students? - Any Sutiadiningsih; Tuatul Mahfud (International Journal of Evaluation and Research in Education (IJERE), 2023)
Entrepreneurial intentions play an essential role in creating new entrepreneurs. There are many methods of teaching entrepreneurship that aim to form entrepreneurial intentions, and one of them is considered suitable to be applied in vocational high schools, namely factory teaching. This study examined the effect of the teaching factory on entrepreneurial intentions through the theory of planned behavior dimension. There were 280 vocational high school students participated in the study. Data was collected via online questionnaires and analyzed with Amos software using the structural equation modeling method. The teaching factory has been shown to influence students’ entrepreneurial intentions both directly and indirectly via mediators of attitudes toward behavior and perceived behavioral control. This study also provided important implications for vocational practitioners to develop a teaching factory learning model as a school business unit based on the needs of the world of work. Good management of the teaching factory is expected to prepare prospective new entrepreneurs from vocational school graduates.